Risks management of infrastructure line services and their impact on the financial costs of road projects in Jordan - Ala'a Sa'dl Issa Alkhawaja; Ibrahim Farouq Varouqa (Measurement: Sensors, 2023)
The Jordanian building sector contributes greatly to the country's GDP. However, Jordanian road projects are notorious for cost overruns throughout construction and operation. Risks to infrastructure services in Jordan are identified, studied, and evaluated in this report. Having this information will make it easier for project stakeholders to effectively manage risks. Additionally, it is trying to find ways to improve the connection between road implementation authorities, government agencies, and the business sector. A list of 32 hazards was compiled based on a literature assessment that analysed the project's managerial, technological, financial, social, location-specific, and operational issues. Engineers and other professionals in Jordan were then requested to complete a survey. Cost overruns on the Jordan Crossing Jordan project have been blamed on eight factors, according to Jordanian experts. More than 300 people were polled to determine the likelihood and magnitude of each possible danger. According to the results of the survey, infrastructure projects are most likely to encounter the greatest number of hazards. Lack of infrastructure is the greatest threat to the project's success, with an effect of 0.862. Problems with the contract between the project's running firm and the government authorities in control; reorganization of corporate structures and processes; and accidents that occur as a result of inadequate safety measures are all possibilities with a RII of 0.858. An essential part of project risk management is the identification and evaluation of potential hazards. In this study, it will be looked at for the first time how risk management strategies affect infrastructure project risks.